The mTOR pathway in reproduction: from gonadal function to developmental coordination. Issue 4 (April 2020) - Correia, Bibiana; Sousa, Maria Inês; Ramalho-Santos, João
Abstract : Reproduction depends on many factors, from gamete quality to placenta formation, to fetal development. The mTOR pathway is emerging as a major player that integrates several cellular processes in response to a variety of environmental cues that are relevant in many aspects of reproduction. This review provides a general overview, summarizing the involvement of the two mTOR complexes (mTORC1 and mTORC2) in integrating signaling pathways, sensing environmental status, and managing physiological processes inherent to successful reproductive outcomes and pluripotent stem cell function. As a well-known governor of multiple cellular functions, it is not surprising that mTOR has a key regulatory role in determining cell quiescence or differentiation. In the gonads mTOR helps maintain spermatogonial stem cell and follicle identity and tightly regulates differentiation in both systems to ensure proper gamete production. The mTOR pathway is also known to prevent premature follicle exhaustion, while also controlling the blood–testis barrier in the male gonad. In stem cells mTOR again seems to have a role in controlling both pluripotency and differentiation, mirrored by its in vivo roles in the embryo, notably in regulating diapause. Finally, although there are clearly more complex systems intertwined in placental function, mTOR seems to serve as an early checkpoint for development progression and successful implantation.